The Effect Of Halal Certification, Social Media And Consumer Awareness On Gen Z's Interest In Buying Halal Cosmetics In Plampang District - Fadlia Galib; Dahlia Bonang (UNIVED Press, 2026)
This study aims to examine the influence of halal certification, social media, and consumer awareness on the purchasing interest of halal cosmetics among Gen Z in Plampang District. Data collection in this study was conducted through distributing questionnaires with a purposive sampling method using a 5-point Likert scale from 98 respondents. The relationship between variables was analyzed using structural equation modeling with a partial least squares approach with the SmartPLS 4.0 statistical tool. The results of this study show that halal certification, social media, and consumer awareness have a positive and significant effect on the purchasing interest of halal cosmetics among Gen Z in Plampang District. This finding confirms that these three factors have an important role in driving purchasing decisions for halal cosmetics, so they can be a basis for consideration for industry players and marketers in designing more effective marketing strategies in the future.